PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN REMUNERASI TERHADAP KINERJA PEGAWAI PADA KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK JAWA TIMUR I - Mohammad Imam Zulkarnain (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2016)
Employee performance is a benchmark for a person's success in carrying out its duties. Performance influenced by several factors, both from the employees themselves are self-motivation, as well as from outside himself as leadership and remuneration. This study aims to determine whether there is influence of leadership, work motivation and remuneration of the employee's performance at the Regional Office of Directorate General of Taxation East Java I, either partially or simultaneously. And to determine which factors most influence on employee performance at the Regional Office of Directorate General of Taxation East Java I. This research was conducted at the Regional Office of Directorate General of Taxation East Java I with a sample of 100 people. The independent variable is leadership (X1), work motivation (X2), and remuneration (X3), while the dependent variable is the performance (Y). Data using multiple regression analysis. After analysis and verification of hypotheses, then the conclusions in this study are: Calculation partially explained as follows: 1) leadership (X1) = 4.515 t count > t table = 1.984; 2) work motivation (X2) t = 5.717> t table = 1.984; 3) remuneration (X3) t = 2.044> t table = 1.984. So leadership, work motivation and remuneration partially have significant influence on the performance of employees in the Office of the Directorate General of Taxes in East Java I. So the first hypothesis is accepted. Multiple linear regression calculations yield the value of F = 45.264, while the magnitude of the F table = 2.70 level of significant (a) of 5%. So leadership, motivation, and remuneration together have a significant effect on the performance of employees in the Office of the Directorate General of Taxes in East Java I. This means that both the proposed hypothesis is accepted. Based upon the results of the standardized beta coefficient of each independent variable is known that the dominant variables that affect the performance of employees in the Office of the Directorate General of Taxes in East Java I is indicated by the motivation to work with the highest beta coefficient of 0.465.Keywords: Leadership, Work Motivation, Remuneration, Performance